PENERAPAN PENGENDALIAN KUALITAS (QUALITY CONTROL) PADA PROSES PRODUKSI KOPI ROBUSTA (Studi Kasus: Kopi Partungkoan Tarutung, Tapanuli Utara, Sumatera Utara) - Yohana Esfrensa Millenia Indah Simatupang; Sulistyodewi Nur Wiyono; Elly Rasmikayati; Pandi Pardian (Universitas Galuh Ciamis, 2021)
The level of consumption and the number of coffee processing industries is increasing so that competitiveness is also getting higher. Product quality is a factor that affects business competitiveness, but Partungkoan Tarutung Coffee as a ground coffee processing industry still find product defects in the production process. This study aims to determine product quality control. This research method used descriptive qualitative with case study research techniques. The analytical tools used were descriptive statistics and Statistical Process Control (SPC). Sampling using purposive judgment sampling technique to determine respondents that consists of business owners and daily production workers and thirty consumers of UMKM Coffee Partungkoan Tarutung. The results showed that the product quality control was under control because it was within the upper control limit (UCL) and the lower control limit (LCL)